2022
DOI: 10.2147/jir.s348850
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-13 Attenuates Lipopolysaccharide-Induced Inflammatory Responses and Acute Lung Injury by Regulating PFKFB3-Driven Glycolysis Induced by NOX4-Dependent ROS

Abstract: Purpose Acute lung injury (ALI) is a life-threatening condition with limited therapeutic options. Macrophage inflammation plays a key role in the development of ALI. Abnormal glycolysis of macrophages contributes to the inflammatory response. However, the role of macrophage glycolysis in ALI still requires investigation. Apelin-13 has been shown to protect against ALI, whereas the underlying mechanisms remain unclear. In this study, we explored the effect of apelin-13 on lipopolysaccharide (LPS)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…The inhibition of PKC or NOX4 attenuated Pseudomonas aeruginosa -induced lung inflammatory injury by inhibiting ROS production [ 40 ] and LPS-induced ALI by inhibiting apoptosis and secretion of proinflammatory cytokines in pneumonia cells [ 41 ]. Serum apelin-13 could protect against sepsis-induced ALI by regulating NOX4-dependent ROS [ 42 ]. NOX4 (versus other NOX isoforms) was specifically involved in damage of the endothelial cell barrier in the lungs of a mouse model of CLP-induced sepsis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of PKC or NOX4 attenuated Pseudomonas aeruginosa -induced lung inflammatory injury by inhibiting ROS production [ 40 ] and LPS-induced ALI by inhibiting apoptosis and secretion of proinflammatory cytokines in pneumonia cells [ 41 ]. Serum apelin-13 could protect against sepsis-induced ALI by regulating NOX4-dependent ROS [ 42 ]. NOX4 (versus other NOX isoforms) was specifically involved in damage of the endothelial cell barrier in the lungs of a mouse model of CLP-induced sepsis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…APJ is the endogenous receptor of apelin, and apelin-13 is the most active ligand of APJ 22 . In LPS-induced ALI, apelin can effectively improve the inflammatory response of lung tissue and reduce mortality in mice 23 . However, the exact molecular mechanism by which apelin acts is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Apelin, a group of small peptides, is an endogenous ligand for angiotensin type 1 receptor associated protein. Yuan et al have demonstrated that apelin-13 can regulate ROS and inhibit glycolysis of macrophages, thereby reducing the release of in ammatory cytokine and improve acute lung injury 24 . Our GSEA analysis also further corroborated the above results.…”
Section: Discussionmentioning
confidence: 99%